2017
DOI: 10.1088/1361-6463/aa54de
|View full text |Cite
|
Sign up to set email alerts
|

Observation of complex magnetic behaviour in calcium doped neodymium manganites

Abstract: Crystal structure and magnetic properties of polycrystalline Nd1−xCaxMnO3 (x  =  0.0, 0.2, 0.3, 0.33, 0.4, 0.5, 0.6 and 0.8) manganites were investigated. The fine structural refinement using GSAS was found to undergo a transition from Pnma reflections to Pbnm reflections associated with the Ca substitution at x  =  0.3. The magnetic ordering of these compounds witnessed distinct magnetic phases with variations of Ca substitution. Magnetic ordering of the parent compound, NdMnO3, was found as A-type antiferrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 54 publications
4
9
0
Order By: Relevance
“…The temperature at which onset of CO phase takes place in the material has been designated as T CO and as a consequence a broad cusp is visible in the temperature‐dependent magnetization curve. In the present case, it has been found that the cusp is around 240 K and the observed T CO value is in good agreement with the reported values for half‐doped NCMO manganite . The large anomaly found around T CO is also visible in the first derivative of FC curves around T CO (shown in inset of Figure (a)).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The temperature at which onset of CO phase takes place in the material has been designated as T CO and as a consequence a broad cusp is visible in the temperature‐dependent magnetization curve. In the present case, it has been found that the cusp is around 240 K and the observed T CO value is in good agreement with the reported values for half‐doped NCMO manganite . The large anomaly found around T CO is also visible in the first derivative of FC curves around T CO (shown in inset of Figure (a)).…”
Section: Resultssupporting
confidence: 92%
“…In the present case, it has been found that the cusp is around 240 K and the observed T CO value is in good agreement with the reported values for half-doped NCMO manganite. [7,26] The large anomaly found around T CO is also visible in the first derivative of FC curves around T CO (shown in inset of Figure 3(a)). Even though, the anomaly is not visible from M-T curves of nano sample, a zoomed derivative curve shows the signature of CO anomaly around 240 K (inset of Figure 3(b)).…”
Section: Magnetic Propertiesmentioning
confidence: 78%
See 2 more Smart Citations
“…res.in; vasu.mutta@gmail.com; Tel: +91 4712515491 properties due to the difference in the average A-site ionic radius. [22][23][24][25][26][27] It is understood that, in doped manganites, the double exchange (DE) interaction via the Mn 3+ -O 2À -Mn 4+ ions is responsible for the ferromagnetic (FM) behaviour and the superexchange (SE) interaction through Mn 3+ -O 2À -Mn 3+ and Mn 4+ -O 2À -Mn 4+ ions are responsible for the antiferromagnetic (AFM) behaviour. This indicates that the strength of the competing exchange interactions and magnetic properties are eventually affected by different factors such as rare Earth substitution at the A-site, replacement of manganese by other transition elements, the introduction of deciency at A and A 0sites, etc.…”
Section: Introductionmentioning
confidence: 99%